Carencia afectiva paternal y su incidencia en el comportamiento de un adolescente de 15 años de edad en la ciudad de Babahoyo - Sarco Gomez, Diana Carolina (2022)
The purpose of this research is to determine the condition of paternal affective deprivation and its impact on the behavior of a 15-year-old adolescent from the city of Babahoyo based on family conflict such as: the separation of the parents and constant fights in the family, the absence of affection is a problem since in the long run it affects the emotional state of the adolescent in which it is reflected in the behavior of the patient, in the development of the case they were collected important data for the progress of the study and its respective preparation; Techniques were applied according to the symptomatology such as: psychological interview and clinical observation, while psychometric tools such as: clinical history and complementary tests were very helpful in reaching a presumptive diagnosis such as intermittent explosive disorder in order to obtain good results. At the same time, provide support and guidance throughout the therapy process to the adolescent through which cognitive behavioral therapy was worked on, where excellent results were provided, such as having control of thoughts, emotions of behavior, while the systemic approach helps to improve family relationships by promoting implicit communication.